Novel Insights Into the Potential Mechanisms of N6-Methyladenosine RNA Modification on Sepsis-Induced Cardiovascular Dysfunction: An Update Summary on Direct and Indirect Evidences - Wang, Yang; Xu, Miaomiao; Yue, Peng; Zhang, Donghui; Tong, Jiyu; Li, Yifei (Frontiers in Cell and Developmental Biology, 2021)
Sepsis is a life-threatening organ dysfunction caused by a host’s dysfunctional response to infection. As is known to all, septic heart disease occurs because pathogens invading the blood stimulate the activation of endothelial cells, causing a large number of white blood cells to accumulate and trigger an immune response. However, in severe sepsis, the hematopoietic system is inhibited, and there will also be a decline in white blood cells, at which time the autoimmune system will also be suppressed. During the immune response, a large number of inflammatory factors are released into cells to participate in the inflammatory process, which ultimately damages cardiac myocytes and leads to impaired cardiac function. N6-methyladenosine (m6A) is a common RNA modification in mRNA and non-coding RNA that affects RNA splicing, translation, stability, and epigenetic effects of some non-coding RNAs. A large number of emerging evidences demonstrated m6A modification had been involved in multiple biological processes, especially for sepsis and immune disorders. Unfortunately, there are limited results provided to analyze the association between m6A modification and sepsis-induced cardiovascular dysfunction (SICD). In this review, we firstly summarized current evidences on how m6A mediates the pathophysiological process in cardiac development and cardiomyopathy to emphasize the importance of RNA methylation in maintaining heart biogenesis and homeostasis. Then, we clarified the participants of m6A modification in extended inflammatory responses and immune system activation, which are the dominant and initial changes secondary to sepsis attack. After that, we deeply analyzed the top causes of SICD and identified the activation of inflammatory cytokines, endothelial cell dysfunction, and mitochondrial failure. Thus, the highlight of this review is that we systematically collected all the related potential mechanisms between m6A modification and SICD causes. Although there is lack of direct evidences on SICD, indirect evidences had been demonstrated case by case on every particular molecular mechanism and signal transduction, which require further explorations into the potential links among the listed mechanisms. This provides novel insights into the understanding of SICD.